"It's our Scotland just as much as anyone else's". Issue 1 (4th January 2016) - Hood, Ian
Abstract : Purpose: – The purpose of this paper is to look at some of the experiences of people with learning disabilities in Scotland during the Independence Referendum campaign, through the prism of a series of workshops run by a collective advocacy organisation. These workshops took an inclusive approach to the views of everyone with a learning disability. Design/methodology/approach: – This paper is a record of the workshops written after the event. Findings: – People with learning disabilities were engaged in the discussion and campaigns around the referendum in similar ways to other members of their communities. The issues that especially affect people with learning disabilities figured highly in the workshops. However, there was also discussion of more general issues such as employment, jobs and constitutional arrangements that affect all citizens. Research limitations/implications: – This is an observational study written up by the workshop leader and, as such, can make no claims of complete impartiality. Practical implications: – Experience of the workshops suggests that many of the barriers that prevent civic participation of people with learning disabilities may be ones of staff attitude and approach. The support offered to enable people to take part in the community may on some occasions have the opposite effect. Social implications: – Nonetheless, for those who have been able to overcome these barriers, there are signs of much greater participation in public life. This reflects an ongoing process of change with many people now joining political parties or being able to make contributions towards political debate. Originality/value: – This paper provides an important record of the growing involvement of people with learning disabilities in civil society.